Bilateral Variations in Median Nerve Formation with Embryological Basis and Clinical Correlation - Bikash Chandra Satapathy; Soumitra Trivedi (Academia Anatomica International, 2016)
During routine dissection of upper limb of a 68 year old male cadaver bilateral variations in median nerve were observed. On the left side the lateral cord pierced coracobrachialis without giving the lateral root of median nerve and after coming out of coracobrachialis it bifurcated in to musculocutaneous nerve and lateral root of median nerve. The medial root of median nerve continued up to the middle of arm and joined the lateral root and formed the median nerve in the middle of arm instead of axilla. On the right side there were two lateral roots of the median nerve that joined the medial root to form the median nerve. The musculocutaneous nerve after piercing coracobrachialis gave a communicating branch to the median nerve in the lower part of front of arm. These variations can lead to unusual innervation and entrapment neuropathies. Identification of these variants are valuable during surgeries performed in and around axilla and flexor compartment of arm.